Alkylammonium thiostannate inorganic/organic hybrids as high-performance photocatalysts with a decoupled adsorption–photodegradation mechanism. Issue 27 (17th May 2019) - Hao, Xiufang; Cui, Xiaoyan; Hu, Meiqi; Jia, Yiming; Li, Xinxin; Wei, Shuo; Lu, Jun
Abstract : For traditional photocatalysts, the adsorption and successive surface reaction constitute a coupled and integrated process, owing to the limited number of catalytic active centres available. Abstract : For traditional photocatalysts, the adsorption and successive surface reaction constitute a coupled and integrated process, owing to the limited number of catalytic active centres available. An attempt to boost the photocatalytic performance to optimize the adsorption and surface reaction process may be performed by exploring various photocatalyst infrastructures. Herein, we use a facile solvothermal method to synthesize a series of layered alkylammonium thiostannate hybrids, namely (baH)2 Sn3 S7, (haH)2 Sn3 S7 and (oaH)2 Sn3 S7 (ba = butylamine, ha = hexylamine, oa = octylamine). The hybrids showed broad UV-visible light absorption with appropriate band gaps. The inorganic/organic amphiphilic infrastructure of these hybrids enables them to exhibit prominent ion-exchange properties for Rhodamine B, with a large capacity over a wide pH range (1–11). And the adsorbed Rhodamine B is photodegraded within 30 minutes. A mechanistic study indicates that the adsorption and photodegradation steps are performed at the organic and inorganic layers within these hybrids, respectively, which are decoupled and independent. We conclude that the high-performance integrated adsorption–photodegradation ability is a consequence of the lipophilicity of intercalated alkylammonium and the photocatalysis performance of the 2D [Sn3 S7 ] n 2 n − monolayers.